Alfamart brand communication on expansion retail business in the Philippines - Ashri Fatria; Daniel Susilo; Rismi Juliadi (Jurnal Komunikasi Profesional, 2022)
ABSTRACT In a guideline, the global brand company is broadly positioned around the world. In case the brand could be a premium estimated brand, it could be a premium cost around the world. The application of a global brand ought to too be indivisible from the part of the branding and key communication that makes difference in companies entering the domain of other countries. But what makes a brand profitable and how profitable is it? What could be a global brand and why are there still neighborhood brands? The spread of the COVID-19 pandemic in Southeast Asia, made global business lines run slowly and had to force business people to rack their brains to survive during a pandemic. The establishment of a lockdown policy has also hampered the distribution of retail goods as one of the impacts of the COVID-19 pandemic. However, it is different from Alfamart, which was able to survive during the pandemic with a decrease in net profit at the end of the third quarter of 2020 with a fairly small figure of -1.85% (Hafiyyan, 2020a). One of the strategies revealed is the expansion of Alfamart received a positive response in the Philippines competing 7-Eleven, Mini-Stop, Allday, Family Mart, and Lawson. So throughout 2020 Alfamart managed to open more than 1.000 new stores in Metro Manila and nearby province. The global brand communication strategy used by Alfamart to deliver strong brand awareness to Filipino customer mind and made Alfamart's brand positioning as a super minimart that serves the community. According to the above exposures, Alfamart is considered a successful brand in Indonesia that expand its global retail business in Southeast Asia since the COVID-19 pandemic that spread throughout the world. It is exciting research, Alfamart has not become the primary choice of consumers to shop at minimart or convenience stores in the Indonesian market itself. It is also inseparable from the brand communication strategy used by Alfamart to build strong brand awareness in Filipino consumers' minds. This research method is the case study, continuing to data analysis using the pattern matching of the informant insights and findings. The authors focus on describing the strategy of Alfamart Philippines to communicate its brand awareness in the community. Then, analyze the pattern matching of Filipino customers’ perceived brand of Alfamart through interviews with informants. The research findings are that Alfamart has expanded rapidly to open more than 1.200 stores since 2014 to help the community at Barangay (a remote area of the Philippines) for jobs and serve groceries product especially frozen food so that Alfamart become an "extended pantry" to their home. Alfamart’s accessibility and brand positioning as super minimart for Filipino customers built strong brand awareness as a global brand from Indonesia.